2016
DOI: 10.1002/lary.25897
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of racial differences in survival for sinonasal cancer

Abstract: 2c. Laryngoscope, 126:2022-2028, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 24 publications
2
21
1
Order By: Relevance
“…In fact, a recent national surveillance report indicated that of all cancers in the United States, the black versus white difference in survival was worst among head and neck cancer except for melanoma and uterine cancer . Previous studies have been inconclusive about the association between race and sinonasal cancer, especially the black versus white comparison; many have found any suggested association attenuated after adjusting for important tumor and clinical factors; however, we found that the association between race and all‐cause mortality among sinonasal cancer patients in our study remained statistically significant after controlling for important clinical risk factors, including histology, stage of presentation, treatment modality, and comorbidity. One difference between ours and previous studies is that we did not only control for clinical factors, we also accounted for the time‐varying nature of treatment modalities, which provides a more accurate picture of treatment plan since there are usually waiting times and delays between cancer treatment modalities .…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations
“…In fact, a recent national surveillance report indicated that of all cancers in the United States, the black versus white difference in survival was worst among head and neck cancer except for melanoma and uterine cancer . Previous studies have been inconclusive about the association between race and sinonasal cancer, especially the black versus white comparison; many have found any suggested association attenuated after adjusting for important tumor and clinical factors; however, we found that the association between race and all‐cause mortality among sinonasal cancer patients in our study remained statistically significant after controlling for important clinical risk factors, including histology, stage of presentation, treatment modality, and comorbidity. One difference between ours and previous studies is that we did not only control for clinical factors, we also accounted for the time‐varying nature of treatment modalities, which provides a more accurate picture of treatment plan since there are usually waiting times and delays between cancer treatment modalities .…”
Section: Discussioncontrasting
confidence: 70%
“…There is likely an interplay of factors driving this racial disparity finding that requires further investigation. A previous study suggested that the driver of the racial disparity in sinonasal cancer mortality is mostly receiving adequate treatment, and earlier stage of presentation . It is important that systemic factors associated with poor access to standard care are understood to increase early stage presentation and receipt of adequate care …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the overall low incidence of sinonasal cancers, database analyses are crucial for understanding the factors that are associated with disease outcomes. Prior studies utilizing the National Cancer Institute's Surveillance, Epidemiology, and End Results (SEER) Program database demonstrated racial differences in survival for sinonasal cancers, specifically in sinonasal SCC . However, there are limited studies describing the role of additional patient and treatment factors on sinonasal SCC survival and short‐term outcomes.…”
Section: Introductionmentioning
confidence: 99%